History of gonadotropin use in controlled ovarian stimulation - Radaković Ćosić, Jovana; Mikovic, Zeljko; Perovic, Milan (Medicinski podmladak, 2023)
The discovery of gonadotropins enabled understanding the complexity of the processes involved in human reproduction. Soon after their discovery gonadotropins were used in the treatment of women with the problem of amenorrhea, anovulation and infertility. This mini-review paper aims to provide historical facts related to the development and application of gonadotropins in reproductive medicine.
Keywords: gonadotropins, history, discovery, infertility